The Violence Intervention Project (VIP): Charlie Rigby in conversation with Roman Gerodimos - Rigby, Charlie (Interdisciplinary applications of shame/violence theory, 2022)
Charlie Rigby, Founder and CEO of the Violence Intervention Project (VIP), has worked with young people since 1996 in a variety of social settings, including activity camps, youth centres, social services and youth justice. He founded the VIP in 2017 with the aim to develop therapeutic relationships with vulnerable young people outside of conventional clinical settings; delivering one-to-one support to young people in the community. In this conversation, Rigby reflects on the organisation’s shame-informed intervention work. We start by introducing the work and approach of the VIP, exploring different techniques of approaching and working with clients, the range of day-to-day practical tasks that the project team are involved in, and the challenges facing both the young clients and the team. We then focus specifically on shame as the root of violent behaviour. The central role of shame awareness in the VIP’s approach allows it to avoid a common pitfall of top-down approaches, which directly or indirectly shame young people who are at risk, therefore further widening the gap between them and the system. We also look at specific ways of operationalizing shame: from identifying it as an issue in specific cases or during a conversation, to exploring its root causes and triggers, to trying to address it via raising shame awareness. This is the first account of the VIP’s award-winning work, which provides exciting shame-oriented intervention models for other similar organisations.